(untitled) (Africa Development, 2021)
Contents The Impact of Non-formal Education on Skills and Knowledge of Community Development Workers: A Case Study Derica Alba Kotzé .............................. 1 Critical Reflections on the Joint Africa-EU Strategy Maria Ölund .......................... 15 Globalisation, Economic Reforms and Democracy in Nigeria Chuku Umezurike .......................... 25 Challenges for the Opposition and Democratisation in Tanzania: A View from the Opposition Jonas Ewald & Lennart Wohlgemuth ............. 63 Le développement du sport de performance au Bénin : de l’analyse d’un modèle à un essai de problématique globale Gouda Souaïbou & Georges Kpazaï ................. 97 Irregular Migration and Vulnerability to HIV&AIDS: Some Observations from Zimbabwe France Maphosa.............................. 119 The Youth and Political Ideology in Ghanaian Politics: The Case of the Fourth Republic Ransford Edward Van Gyampo ................... 137 RSE et justice sociale : le cas des multinationales pétrolières dans le Delta du Niger Hervé Lado & Cécile Renouard ................... 167 Participatory Development and Non-Governmental Organisations in Sudan: Expectations and Realities Nawal El-Gack .......................... 195 Les extrémismes développementalistes et leurs conséquences sur les pratiques de développement en Afrique subsaharienne Thierry Amougou ......................... 209